Keong Sulawesidrobia sp Kandidat Kompetitor Inang Perantara Schistosoma japonicum Di Dataran Tinggi Bada Kabupaten Poso: Sulawesidrobia sp Snails as Competitor Candidates for Intermediate Hosts of Schistosoma japonicum in the Bada Highlands of Poso Regency - widjaja, Junus; Satrija, Fadjar; Ridwan, Yusuf; Garjito, Triwibowo Ambar (Perkumpulan Entomologi Kesehatan Indonesia, 2025)
Schistosomiasis, a disease caused by the trematode worm Schistosoma japonicum, with the intermediate host snail Oncomelania hupensis lindoensis, is a complex issue that requires ongoing investigation. The Bada highlands of Poso Regency, one of Indonesia's endemic areas, was found to be an endemic area for schistosomiasis in 2008 due to the presence of cases in humans and the intermediate host snail O. h. lindoensis. This article discusses the Sulawesidrobia sp snail, a significant finding in the Bada endemic area. Surveys were conducted on the same O. h. lindoensis snail habitat in 2017 and 2019, using the man per minute and crushing methods. In 2019, the Sulawesidrobia sp snail habitat was more dominant, with as many as 22 habitats, and the type of habitat was the same as the type of O. h lindoensis habitat. This led to a decrease in the habitat of O. h lindoensis. Sulawesidrobia sp snails, with their small shells, slightly convex circles, and two red lines, were found to inhabit water channels in gardens, rice fields, and ponds, highlighting the need for further research in this area.